Optimization of Business Plan in Creating the Creativity of Home Business Actors in Aisyiyah Members - Nur Isna Inayati; Kurnia Ritma Dhanti; Ira Hapsari (Journal of Society, Community and Business Development, 2023)
The Indonesian nation, including Muslim women's movements such as Aisyiyah, is faced with the challenges of very complex problems and dynamics of social change. For example, the problem of poverty, and violence against women and children. There are several obstacles for women in increasing their business, including not understanding the business plan in doing business. As we know today technology continues to develop and telecommunications are increasingly innovating. With advances in the field of information and communication technology today, the world no longer knows boundaries, distance, space and time. The internet has had a great impact because it created a new paradigm in entrepreneurship and business. Community Service Activities the Science and Technology Program for the Community with the title "Optimizing Business Plans in Creating Creativity for Home Business Actors in Aisyiyah Members" in Banyumas Regency has been carried out smoothly and well. The participants of the socialization were able to receive the socialization that was delivered well, was active and as expected. There is interest from participants to know more so that later it is hoped that it will increase the creativity and understanding of participants in doing business.